The Impact of Child and Maternal Health Indicators on Female Labor Force Participation after Childbirth: Evidence for Germany - Annalena Dunkelberg; Christa Katharina Spieß (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This paper analyzes the influence of children's health and mothers' physical and mental wellbeing on female labor force participation after childbirth in Germany. Our analysis uses data from the German Socio-Economic Panel (SOEP) study, which enables us to measure children?s health based on the occurrence of severe health problems including mental and physical disabilities, hospitalizations, and preterm births. Since child health is measured at a very young age, we can rule out any of the reverse effects of maternal employment on child health identified in US studies. Within a two-year time period, we investigate the influence of these indicators on various aspects of female labor force participation after childbirth, including continuous labor force participation in the year of childbirth and the transition to employment in the year following childbirth. Since the majority of women in Germany do not go back to work within a year after childbirth, we also investigate their intention to return to work, and the preferred number of working hours. We find that the child?s severe health problems have a significant negative effect on the mothers' labor force participation and a significant positive effect on her preferred number of working hours, but that hospitalizations or preterm births have no significant effect. For the mothers' own health, we find a significant negative effect of poor mental and physical wellbeing on female labor force participation within a year of childbirth. To our knowledge, this is the first empirical study of this kind on data outside the US.
Keywords: I19; J23; J22; 330; Female labour supply; childhealth; well-being; Mütter; Kinder; Gesundheit; Frauenerwerbstätigkeit; Arbeitsangebot; Deutschland